The Strategi Branding Program Jalan Jalan Kompas TV di Era Konvergensi Media - Khadijah Najma Zahirah; David Rizar Nugroho (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Era of media convergence, television programs are required to integrate traditional broadcasting with digital platforms to maintain their relevance. This study explores the branding strategies of the Jalan Jalan program by Kompas TV across Instagram, Youtube, and Tiktok. Using a qualitative descriptive method with participatory observation, the research examines how the program adapts its content for each platform based on their unique characteristics and audience behavior. The study reveals that Jalan Jalan employs platform specific strategies, such as short-form video teasers on Instagram, full episodes with personalized visual elements on YouTube, and bite-sized, engaging travel content on TikTok. These strategies reflect an understanding of media convergence through multi-platform storytelling and audience interaction. The findings highlight key challenges such as content competition and unstable algorithms, alongside opportunities like viral exposure and collaborative branding. This research contributes to strategic communication studies by providing insights into adaptive branding practices in the digital media landscape..